González Vázquez, Nila ed. 2009: The Tale of Gamelyn of The Canterbury Tales. An Annotated Edition - Guzmán, Trinidad (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen